The degree of availability of reflective thinking skills in the content of rhetoric in the Arabic Language and Literature textbook for the first year of high school (Journal of Hama University, 2025)
The research sought to determine the degree of availability of reflective thinking skills in the Arabic language textbook for the first year of secondary school. For this purpose, the research relied on the descriptive approach based on the content analysis method by analyzing the content of rhetoric for the first year of secondary school, relying on the content analysis form based on reflective thinking skills. There are (31) sub-skills distributed over five main skills: contemplation and observation, revealing fallacies, arriving at conclusions, giving convincing explanations, and developing suggested solutions. The research concluded that the number of contemplative thinking skills in the content of rhetoric in the Arabic Language and Literature book for the grade The first secondary had 75 occurrences, and reflective thinking skills were considered to a weak degree, and in close proportions among them. The skill of giving convincing explanations was in first place, with a percentage of (24.77%), followed by the skill of arriving at conclusions with repetition, with a percentage of (16.81%), comes in second place. The skill of detecting fallacies comes in third place, with a percentage of (9.73%), and occupies the skill. Contemplation and observation ranked fourth with a rate of (8.84%). The skill of developing proposed solutions came in fifth and last place with a rate of (6,19%), The results indicated a deficiency in the content of rhetoric in the Arabic Language and Literature book for the first year of secondary school in considering the inclusion of reflective thinking skills. The degree of availability of these skills reflects the neglect of those responsible for writing the content of rhetoric in the book.
Keywords: reflective thinking skills, rhetorical content, Book of Arabic Language and Literature. reflective thinking skills, rhetorical content, Book of Arabic Language and Literature.